Prof. James R. Wait and mining production technology-an appreciation. - Tripp, A.C (IEEE Transactions on antennas and propagation)
Prof. James R. Wait (1951, 1953, 1967) examined electromagnetic (EM) wave propagation in many situations of interest to mining production, including propagation in tunnels, propagation along extended conductors such as cables and drill stems, and propagation in coal seams. This work remains relevant, both to the mining engineer interested in the EM environment of an operating mine and to the electrical engineer interested in verifying new computational techniques and in extending the scope of EM technology in mining production. Late work in EM focussing in a geological environment is relevant to ?next generation? geophysical monitoring equipment